PC.107 Do Words Matter?. (9th June 2014) - Doerr, A; Eastwood, K; Jones, R; Mannix, P; Cairns, P
Abstract : Introduction: Reorientation of care decisions are a core part of neonatology. While the majority die rapidly after a decision has been made, a proportion may live for days or weeks. Clear communication of an end of life plan is vital in emergencies. We compared two forms available across Bristol neonatal units. Methods: We surveyed a cross section of medical and nursing staff. The first was the trust standard paediatric form entitled 'Do not attempt cardiopulmonary resuscitation' (DNACPR). The second; a simple form entitled 'Allow natural death'. There was a clear statement that the baby would not be for resuscitation along with spaces to document what the parents did and didn't want in the event of acute deterioration. We investigated perceived ease of use in discussions with the parents and in a subsequent emergency. Results: 89% preferred the phrase 'allow natural death' rather than 'do not attempt cardiopulmonary resuscitation'. 93% thought that the simple form would be adequate in a emergency whereas only 44% felt that the complex form would be easy to follow. Most agreed that both were appropriate for a NICU, however the complex form was thought to have too much detail. More than half felt that the complex form would be distressing and confusing to parents, whilst feelings regarding the simple form included sadness, acceptance and understanding. Conclusion: The use of an allow natural death approach which allowed parents to document how they wanted their baby to die was more acceptable to neonatal staff than a DNACPR form.